Ciclagem de nutrientes em área de restauração de floresta ombrófila densa das terras baixas - Moreira, Fagner Luciano (2014)
Despite being one of the most biodiverse biomes, the Atlantic Forest for centuries faces the degradation caused by the disordered occupation of the land. The liabilities generated are huge, which demands studies to enable their recovery. The study of nutrient cycling is fundamental, because it provides a better understanding of the nutrients dynamic in the ecosystem, moreover it is an important indicator of recover degraded areas. This way, this work aimed to study the cycling of nutrients in different methods of restoring the Lowlands Tropical Rain Forest, in Vale Natural Reserve, Linhares, ES, between March 2013 and January 2014. The studies of accumulated litter and soil chemical properties were conducted in six treatments (restoration methodologies), compounds by a combination of factors spacing (2x2 3x3 m) and species richness (species numbers per treatment: 29, 58 and 114). The collecting of accumulated litter occurred in March and August 2013, the highest and lowest precipitancy seasons, respectively. The litter was compartmentalized into two fractions (leaves + miscellaneous and branches), quantifying biomass, nutrients content and tenor. Soil collecting to study its chemical attributes occurred in March 2013, with samples taken at depths of 0-5 cm, 5-10 cm, 10-20 cm and 20-40. Otherwise, the study of the redistribution of nutrients is restricted to two species (Bixa arborea Huber. and Joannesia princeps Vell) of relevant interest for forest restoration, performed in three treatments, which differed only in terms of species richness, and spacing was the same for all. In each treatment were collected leaves from the canopy of five exemplars of each of the two species and from the collectors established beneath their canopies, in October 2013 (lowest precipitancy season) and in January 2014 (highest precipitancy season). From the material collected, were determined the nutrients levels and values of redistribution were calculated. Regarding Chapter I, the methodologies of restoration did not affect the soil chemical properties and litter; The largest accumulation of biomass and nutrients level from the litter fractions occurred in the lowest precipitancy season; the low biomass accumulation and nutrient content of litter associated with low soil fertility indicated that the restoration project is close to the patterns of ecosystems in the process of recovery. In relation to Chapter II, the treatments did not influence in the levels of most of the leaves nutrients from the two species in both times; nutrients redistribution of J. princeps tended to be higher in the lower precipitancy period, and B. arborea tended to be higher in the highest precipitation season; the species showed an efficient redistribution of nutrients, showing great potential in forest restoration.